SOSIALISASI SISTEM PERINGATAN BANJIR SEBAGAI UPAYA PENANGGULANGAN BANJIR DI DESA PANTAI HARAPAN JAYA - Muhammad Weshfi; Rafika Rahmawati; Ria Marginingsih (An-Nizam, 2023)
Harapanjaya Beach Village is located close to rivers and beaches which often cause flooding. Floods that often occur are in the form of tidal floods and dispatch floods which cause obstructions to access to and from the village. The water level at some points could reach one meter from the ground, forcing residents to evacuate. To minimize the impact received, a flood warning system is needed by considering the water level in rivers, sea water and also rainfall. This flood warning system works by using simple materials in the form of PVC pipes, flip flops, and alarms which will be installed on the river banks. This system can prevent excessive material and human losses and can save electronic goods. After socialization, residents, especially young people, know how the flood warning system works so they can expand the use of a simple flood warning system. The implementation of community service has an impact, namely increasing the knowledge of young people in making simple flood alarms, reducing material and physical losses due to overflowing floods, and being wary of electronic goods when floods strike.